Respostas
respondido por:
3
Olá!
Temos:
f(x) = 1-x/1+x
Então:
f(2) = 1-2/1+2 = -1/3
f(f(2)) = 1-f(2)/1+f(2) = 1+1/3 / 1-1/3 = 4/3 / 2/3 = 4/3.3/2 = 2
Logo, queremos:
f(f(f(2))) = f(2) = 1-2/1+2 = -1/3
Espero ter ajudado! :)
Temos:
f(x) = 1-x/1+x
Então:
f(2) = 1-2/1+2 = -1/3
f(f(2)) = 1-f(2)/1+f(2) = 1+1/3 / 1-1/3 = 4/3 / 2/3 = 4/3.3/2 = 2
Logo, queremos:
f(f(f(2))) = f(2) = 1-2/1+2 = -1/3
Espero ter ajudado! :)
respondido por:
0
o valor do resultado vai ser 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás